If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -38 = 14x + 2 Reorder the terms: -38 + 9x = 14x + 2 Reorder the terms: -38 + 9x = 2 + 14x Solving -38 + 9x = 2 + 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. -38 + 9x + -14x = 2 + 14x + -14x Combine like terms: 9x + -14x = -5x -38 + -5x = 2 + 14x + -14x Combine like terms: 14x + -14x = 0 -38 + -5x = 2 + 0 -38 + -5x = 2 Add '38' to each side of the equation. -38 + 38 + -5x = 2 + 38 Combine like terms: -38 + 38 = 0 0 + -5x = 2 + 38 -5x = 2 + 38 Combine like terms: 2 + 38 = 40 -5x = 40 Divide each side by '-5'. x = -8 Simplifying x = -8
| 0.14y+0.07(y+2000)=2030 | | 26=14-6c | | 4x-2+6x=18 | | 4x-1,4=2x+4 | | s(t)=-16t^2+48t+30 | | 5x-16=4x-3 | | x-1/5x=64 | | 2(4+3x)=2(2x+5) | | 7(3x+13)+4(x+9)=252 | | 3/5(x=y)-1/5(x-1)= | | x+(x*.14)=700 | | y=(4x+7)(3x-8) | | 235=5(x-50)+60 | | 2=144 | | 5y/7-9/14=y/2 | | 5a^2b^6/20a^4b^2 | | 5-9[5-(8y-7)]= | | -16t^2+48t+30=0 | | 7/9x-5/6x=2 | | (2x-3)-(5x-5)= | | 3z-4=12 | | 3z-4=7.5 | | (2x-3)+(5x-5)= | | 3z-4=9 | | x+2+x=210 | | 2j-1=9 | | 9b^4-16=0 | | 7w+4x-4y-x-2w+3y-3x+4w= | | 2x+2=-11 | | 1+6x=7x-4 | | (9x+2)=3x-22 | | 32(x-1)=-8(4x-x)+24x |